Korelasi Kecenderungan Berpikir Kritis dengan Hasil Belajar IPA Peserta Didik SMP Negeri Se- Lombok Barat - Rina Mindi Safitri; Yayuk Andayani; Jamaluddin Jamaluddin (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2020)
Disposition of critical thinking is one of the main objectives of learning in the 2013 curriculum that expects students to have characters. This study aims to analyze the correlation between the disposition of critical thinking with the learning result of IX grade students for State Junior High School in West Lombok. The sample of this study consisted of 326 students who came from 12 State Junior High School in West Lombok. The research method used is correlational with the adoption and adaptation of the California Critical Thinking Disposition Inventory questionnaire in 2010 to measure critical thinking trends, and secondary data from the documentation of each respondent school. Based on the data analysis, student's critical thinking disposition are in the Ã¢â¬ÅpositiveÃ¢â¬Â category and for learning result are in the Ã¢â¬ÅgoodÃ¢â¬Â category. There is a weak correlation between Disposition Of Critical Thinking with Sains Learning Result which has a correlation value 0.212.